Tasya Farasya’s Credibility as Influencer and “Tasya Farasya Approved” Logo as Endorsement Effect Impact Followers’ Purchase Intention - Suwandy, Tasya Julia; Heksarini, Ariesta (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of influencer credibility and endorsement of the "Tasya Farasya Approved" logo on the buying interest of Tasya Farasya's followers1. Using a quantitative approach, data was collected from 87 respondents who were followers of Tasya Farasya and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of the study show that endorsements through the "Tasya Farasya Approved" logo have a positive and significant influence on the buying interest of followers. However, influencer credibility was partially found to have no significant effect on buying interest in the context of this study44. This shows that product validation labels are more dominant in influencing purchasing decisions than the personal attributes of the influencers themselves